Magnetic Resonance Imaging for the diagnosis and management of acute colonic diverticulitis: a review of current and future use. Issue 3 (19th February 2021) - Jerjen, Franziska; Zaidi, Tooba; Chan, Shannon; Sharma, Ajay; Mudliar, Reuel; Soomro, Khadija; Jimenez, Yobelli; Reed, Warren
Abstract: Diverticular disease is one of the most common causes of outpatient visits and hospitalisations across Australia, North America and Europe. According to the Gastroenterological Society of Australia (GESA, 2010), approximately 33% of Australians over 45 years of age and 66% over 85 years of age have some form of colonic diverticulosis. Patients with colonic diverticulosis are known to develop subsequent complications such as acute colonic diverticulitis (ACD), and when more than one attack of diverticulitis occurs, there is a 70‐90% chance that the individual will experience ongoing problems and recurring infections throughout their lifetime. Medical imaging is fundamental in the diagnosis, treatment and ongoing management of ACD and its complications, with Computed Tomography (CT) identified as the prevailing gold standard in the last few decades. Cross‐database searching highlighted a large gap in the literature regarding the effectiveness of Magnetic Resonance Imaging (MRI) as a non‐ionising radiation alternative imaging tool for ACD imaging after the mid‐2000s, despite ongoing technological advancements in this modality. This narrative review identified 13 key publications (11 primary prospective cohort studies, 1 systematic review and 1 meta‐analysis) that evaluate MRI for ACD imaging, of which five were published within the last decade. Several existing MRI protocols are deemed suitable for ACD imaging, and it is recommended they be re‐evaluated in larger cohorts. Future studies should consider the rapidly growing technological improvements of MRI, its cost efficiency and its applicability in modern day healthcare settings when addressing ACD management. This is especially important considering the gradual rise in radiation dose among the Australian population attributable to increased CT referrals, alongside increased reporting of ACD cases in younger individuals. Abstract : Diverticular disease is one of the most common causes of outpatient visits and hospitalisations. Cross‐database searching has highlighted a large gap in the literature: an absence of publications providing efficacy data on Magnetic Resonance Imaging (MRI) as a non‐ionising radiation alternative for ACD. This narrative review aims to explore available published data and provide an up‐to‐date evaluation of MRI as a tool for the diagnosis and ongoing management of ACD.